Effects of Growth Parameters on the Morphology of CNTs/Cu Composite Powder Prepared Using Cr/Cu Catalyst by Chemical Vapor Deposition. Issue 8 (August 2015) - Shuai, Wang; Ping, Liu; Xiaohong, Chen; Xinkuan, Liu; Wei, Li; Fengcang, Ma; Daihua, He
Abstract: Based on the in-situ polymerization and chemical vapor deposition method (CVD), the synthesis method of CNTs/Cu composite powder was developed by Cr/Cu catalyst via CVD. The crystal phase and micro morphologies of the as-synthesized materials were characterized using scanning electron microscopy (SEM) and Raman spectrum as well as transmission electron microscopy (TEM), respectively. The results show that the superior quality and well-crystallized CNTs/Cu composite powder can be produced by CVD using 10wt% Cr/Cu catalyst at growth temperature as low as 1073 K, for growth time of 30 min and under mixture gas of H2 /C2 H4 with a flow rate of 2450/300 mL/min.